2019
DOI: 10.2196/13127
|View full text |Cite
|
Sign up to set email alerts
|

Using the Unified Theory of Acceptance and Use of Technology (UTAUT) to Investigate the Intention to Use Physical Activity Apps: Cross-Sectional Survey

Abstract: BackgroundMany university students are lacking adequate physical exercise and are failing to develop physical activity (PA) behaviors in China. PA app use could improve this situation.ObjectiveThe aim of this study was to use the unified theory of acceptance and use of technology (UTAUT) to investigate the intention to use PA apps among university students in Guangzhou, China, and how body mass index (BMI) moderates the effects of UTAUT in explaining PA app use intention.MethodsA cross-sectional study was cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 31 publications
(24 reference statements)
7
64
0
1
Order By: Relevance
“…Although some studies show that only perceived usefulness predicts intention to use mHealth technology [ 19 ], most studies show that both perceived usefulness and perceived ease-of-use have a significant impact on intention to use [ 20 , 21 ]. In the context of smartphone fitness apps, most of the studies focused on initial app adoption [ 15 ]. One study that used the TAM framework to predict users’ continuance usage [ 22 ] found that perceived usefulness and perceived ease of use, along with social norms, predicted intentions to continue using a particular fitness app among users.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies show that only perceived usefulness predicts intention to use mHealth technology [ 19 ], most studies show that both perceived usefulness and perceived ease-of-use have a significant impact on intention to use [ 20 , 21 ]. In the context of smartphone fitness apps, most of the studies focused on initial app adoption [ 15 ]. One study that used the TAM framework to predict users’ continuance usage [ 22 ] found that perceived usefulness and perceived ease of use, along with social norms, predicted intentions to continue using a particular fitness app among users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory presents four constructs that determine users’ acceptance and usage behavior: performance expectancy, effort expectancy, social influence, and facilitating conditions. The constructs of the UTAUT have been positively associated with the intention to adopt a fitness app [ 15 ]. UTAUT overlaps with a general theory that explains individual behavior—the Theory of Reasoned Action (TRA) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated factors influencing mHealth use in specific target groups (e.g. [54,55]), for specific diseases or health topics [56][57][58][59][60], and for sustained mHealth engagement [61]. This study aims to explicate the effect of social support.…”
Section: Social Support and Technology-supported Diabetes Selfmanagementmentioning
confidence: 99%
“…While theoretical models of technology adoption (51) are one step towards understanding factors that in uence (mobile) technology adoption and use, there is a gap in proving both signi cant and substantive usage effects for mHealth (52,53). Previous studies investigated factors in uencing mHealth use in speci c target groups (e.g., 54,55), for speci c diseases or health topics (56)(57)(58)(59)(60), and for sustained mHealth engagement (61). This study aims to explicate the effect of social support.…”
Section: Social Support and Technology-supported Diabetes Self-managementioning
confidence: 99%